Addressing severe chronic NCDs across Africa: measuring demand for the Package of Essential Non-communicable Disease Interventions-Plus (PEN-Plus). Issue 4 (3rd January 2022) - Boudreaux, Chantelle; Barango, Prebo; Adler, Alma; Kabore, Patrick; McLaughlin, Amy; Mohamed, Mohamed Ould Sidi; Park, Paul H; Shongwe, Steven; Dangou, Jean Marie; Bukhman, Gene
Abstract: Severe chronic non-communicable diseases (NCDs) pose important challenges for health systems across Africa. This study explores the current availability of and demand for decentralization of services for four high-priority conditions: insulin-dependent diabetes, heart failure, sickle cell disease, and chronic pain. Ministry of Health NCD Programme Managers from across Africa ( N = 47) were invited to participate in an online survey. Respondents were asked to report the status of clinical care across the health system. A care package including diagnostics and treatment was described for each condition. Respondents were asked whether the described services are currently available at primary, secondary and tertiary levels, and whether making the service generally available at that level is expected to be a priority in the coming 5 years. Thirty-seven (79%) countries responded. Countries reported widespread gaps in service availability at all levels. We found that just under half (49%) of respondents report that services for insulin-dependent diabetes are generally available at the secondary level (district hospital); 32% report the same for heart failure, 27% for chronic pain and 14% for sickle cell disease. Reported gaps are smaller at tertiary level (referral hospital) and larger at primary care level (health centres). Respondents report ambitious plans to introduce and decentralize these services in the coming 5 years. Respondents from 32 countries (86%) hope to make all services available at tertiary hospitals, and 21 countries (57%) expect to make all services available at secondary facilities. These priorities align with the Package of Essential NCD Interventions-Plus. Efforts will require strengthened infrastructure and supply chains, capacity building for staff and new monitoring and evaluation systems for efficient implementation. Many countries will need targeted financial assistance in order to realize these goals. Nearly all (36/37) respondents request technical assistance to organize services for severe chronic NCDs.